PENGEMBANGAN LKS BERBASIS KEARIFAN LOKAL UNTUK PENINGKATAN KETERAMPILAN PENYELESAIAN MASALAH SISWA - Husnul Khatimah; Septiana Dwi Utami; Saidil Mursali (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2018)
LKS has been implemented in schools in general and has not presented problems related to local wisdom in learning so that students do not develop their skills. The research objective is to develop LKS based on local wisdom and improve problem-solving skills. The type of research Research and Development that uses a 4D model includes defining, designing, developing, and disseminating. The instruments in the study were validation sheets, learning implementation observation sheets (RPP), observation sheets for problem-solving skills, and student response questionnaires. Data collection techniques used is validation, observation, questionnaire, documentation. The results showed that the development of local wisdom-based LKS was feasible with a validity level of 3.59 (valid / non-revised categories). The implementation of RPP learning with an average value of 88.4% (very good category), problem-solving skills of students with an average value of 75 (good category), with quality improvement reaching at 0.42 (medium category), average value the student response questionnaire is 3.70 (very good category). Based on the above results it can be concluded that the LKS based on local wisdom that has been developed is declared valid/not revised and is feasible to use and can improve students' problem-solving skills.